Integrating project-based learning for enhancing higher education within an outcome-based education framework - Bhagwat, Radhika; Kulkarni, Anagha (International Journal of Evaluation and Research in Education (IJERE), 2025)
Project-based learning (PBL) has emerged as a powerful pedagogical approach within the outcome-based education (OBE) framework that is designed to align educational outcomes with the evolving demands of the 21st century. This research investigates the integration of PBL into an engineering course and focuses on its impact on the overall development of the students. Project-based approach was adapted in the artificial intelligence (AI) course, where 56 and 58 students applied AI concepts to real-world challenges in academic year 21-22 and 22-23, respectively. A structured PBL framework was implemented, systematically dividing the project into stages ensuring progressive learning. Feedback and statistical analysis, including a paired t-test, were conducted to evaluate students’ academic and interpersonal skill improvements. The statistical analysis proved a remarkable improvement in the course assessment marks. Students demonstrated improved problem-solving ability, algorithmic thinking and expertise in AI techniques. The findings exhibited enhanced communication skills, effective presentations, articulation of ideas and peer collaboration. These outcomes indicate the significance of PBL on the holistic development of higher education students, within technical disciplines by equipping students with the necessary skills, mindset, and experience to excel in their professional practice. PBL provides a comprehensive assessment of student’s abilities and fosters collaboration with industry partners thus strengthening ties between academia and industry.